Legal Protection To Crediture To The Warranty Of Changed Living Rights Status Become A Disclosure - Febrian Wardhana (Faculty of Law, University of Mataram, 2018)
This research takes on case study of civil case Number 390K / Pdt / 2016. The purpose of this study is to know and further examine the rationale constructed by the judge in the Supreme Court Decision with the number: 390K / Pdt / 2016, against the cancellation of the Deed of Grant from the parents to their child which made it in the Notary, as well as the implementation of the related judge's decision with the cancellation of the deed of grant and about legal protection against creditors collateral guarantee rights in dispute, when a guarantee which has been encumbered by the mortgage right becomes a dispute due to the transition of the previous rights which has been disputed. The transfer of land right must be in accordance with the correct legal process so that when the land rights are secured to the creditor, the land right will be cleared from disputes in the future. Law enforcers in resolving land rights disputes through litigation or non-litigation are often found that in resolving the dispute it is deemed unfair. As experienced in this case where it is not in accordance with applicable legal provisions. That the cause of the problem of land disputes in this case is the unlawful act that eliminates the status of other siblings and thus loses the right of inheritance due to the transfer of rights with the Grant Deed conducted without the knowledge of other siblings consequential in a dispute.The Land Right in dispute are guaranteed by the creditor where the debtor has defaulted and can not fulfill its obligations so that it will be sold in auction. While the efforts made by the plaintiff are to file a lawsuit to the court for the loss of their rights from the land and obtain their rights on the land of the dispute.